CAN JUNIOR ACCOUNTANTS BE TRAINED TO WRITE BETTER? - Owen, George A.; Gerfen, Richard C. (The Accounting Review, 1951)
Abstract This article focuses on an investigative report on a specialized course in accountant's writing which was offered last year at Northwestern University. The questionnaire which is the core of this report was sent to 62 representative accounting firms located in all parts of the United States. Although the scope of the survey may seem to be limited by the small number of firms involved, a quick glance at their names would show that many of them are national firms with branch offices throughout the country. It is believed, therefore, that the replies are representative and that findings are based upon the thinking of the profession. Emerging from the replies to the questionnaire and from our experience in teaching the trial course, a distinct pattern for a specialized course in writing for accounting majors has been found out. Such a course must be designed to teach the student to do the following things: first, analyze accounting material and formulate ideas based on dear thinking and accurate objectives. Second, set up these thought patterns in simple, precise, concise, reader-adapted prose.